Effectiveness of Adding Probiotic Boster Bio Lacto and Turmeric Flour to Feed on Growth Performance of Benih Bileh Fish (Rasbora sp.) - Pradana, Andika; Ibrahim, Yusran; Mahendra, Mahendra; Febrina, Citra Dina (Universitas Teuku Umar, 2024)
Bileh fish (Rasbora sp) is one of the freshwater endemic fish species whose habitat is in rivers and lakes, this fish is much favored by the community, especially in Aceh for consumption needs because it has a savory taste so that the market for this fish increases every month. The high market demand causes the selling price to be high and so far the market demand is mostly taken from natural catches. This study aims to determine the effect of the addition of probiotics boster bio lacto and turmeric flour on the growth of bileh fish seeds (Rasbora sp). This study used a completely randomized design (RAB) with four treatments, namely P0 (control) P1 (7 ml probiotics and 10 gr turmeric flour / kg feed), P2 (9 ml probiotics and 10 gr turmeric flour / kg feed) and P3 (11 ml probiotics and 10 gr turmeric flour / kg feed). The results showed that there was no significant effect (P>0.05) on the growth of bileh fish (Rasbora sp). The addition of probiotics 9 ml/kg feed is the best dose to produce fish weight gain of 0.13 g, length growth of 1.00 cm, specific growth rate of 1.32%/day, feed conversion ratio of 4.16. However, the best survival rate was found in the addition of probiotics 11 ml/kg feed with a value of 91.7%.